PENGARUH KETERAMPILAN MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 5 PEKANBARU - Yesi Novianti; Gimin Gimin; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed to determine the influence of teachers skill toward learning motivation class XI IPS on economic subjects in SMAN 5 Pekanbaru. The populations of this research is class XI IPS Academic Year 2017/2018 which amounted to 80 people. The samples taken with proportionate stratified census sampling method. The number of the sample was 80 people. The data collection techniques was used questionnaires with scala likert and the data analysis technique was used simple regression. The results of this research learning motivation in class XI IPS highest frequency of presentation scores in the highest category (78.8%) and the teachers’ teaching skills are also high (76,3%). The teachers’ teaching skills affect the students’ learning motivations, the magnitude of influence is Y = 9,782 + 0,839X.Key Words: Teachers Skill, Learning Motivation